2016
DOI: 10.1136/bmj.i404
|View full text |Cite
|
Sign up to set email alerts
|

A 7/7 NHS: what price equity?

Abstract: What are we willing to forgo to rectify unequal outcomes between weekend and weekday admissions? And, harder still, can the NHS justify spending the money to iron out these differences, asks John Appleby

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Increasing levels of medical staffing at weekends to those in the week is not possible without extra doctors and non-medical staff; 4 however, a recent economic analysis suggested that the extra expenditure that this would incur could be more efficiently spent in other areas of healthcare. 5 Our cost analysis is very conservative because we only used data on incremental bed day cost, and were unable to reliably model the extra savings in time avoided by not having to prepare and deliver intravenous medications. Hence, the true cost saving will be greater than our model predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing levels of medical staffing at weekends to those in the week is not possible without extra doctors and non-medical staff; 4 however, a recent economic analysis suggested that the extra expenditure that this would incur could be more efficiently spent in other areas of healthcare. 5 Our cost analysis is very conservative because we only used data on incremental bed day cost, and were unable to reliably model the extra savings in time avoided by not having to prepare and deliver intravenous medications. Hence, the true cost saving will be greater than our model predicted.…”
Section: Discussionmentioning
confidence: 99%
“…More information is needed to understand the cause of the often quoted excess weekend mortality, and so identify the measures likely to keep these costs to a minimum. 9 Both managers and government must recognise and respect the contribution that only the professionals can give to individual patients. The current increasing attempts to de-professionalise clinicians must be reversed; they cannot be treated as technocrats, and until this is recognised and implemented, we believe that professional staff morale, and hence standards of care, will remain low.…”
Section: To Put Patients Firstmentioning
confidence: 99%
“…The closest thing to a formal evaluation of health policy in England is often an impact assessment reported by the Department of Health. Whilst at one point mandated for all new legislation and policy implementation (Shah et al ., 2012), it appears they are no longer compulsory as no assessment was performed for the recent 7-day services policy (Appleby, 2016). Even when performed, impact assessments rarely evaluate cost-effectiveness as defined by NICE (Shah et al ., 2012), with benefits seldom quantified in terms of quality-adjusted life years (QALYs).…”
Section: Introductionmentioning
confidence: 99%